Key driver of textile and apparel industry management: fashion brand ESG and brand reputation - Yu, Heeseung; Ahn, Minhwan; Han, Eunkyoung (Frontiers in Environmental Science, 2023)
The aim of this study was to develop and validate multidimensional criteria that can be used to evaluate fashion brand ESG management. This research used both qualitative and quantitative research methods to derive multi-dimensional and wide-ranging questions that could help explain fashion brand ESG with a high level of detail. A Delphi study was conducted with a group of 30 professionals to derive the initial items for fashion brand ESG management, and these items were used to design a questionnaire that was then administered to 800 consumers. Based on the results of exploratory and confirmatory factor analysis, 13 items were used to construct the scale. Convergent and discriminant validity were also verified between the factors. Finally, it was confirmed that the items on the ESG practices scale significantly affected a fashion brand’s reputation and consumer intention to purchase that brand as mediated by reputation. The results of this research are expected to provide a theoretical framework for future ESG research that can help fashion brands achieve more effective ESG management and increase their reputation and sales.